2001
DOI: 10.1128/aem.67.12.5780-5790.2001
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Functional Gene Arrays for Detection of Selected Genes in the Environment

Abstract: To determine the potential of DNA array technology for assessing functional gene diversity and distribution, a prototype microarray was constructed with genes involved in nitrogen cycling: nitrite reductase (nirS and nirK) genes, ammonia mono-oxygenase (amoA) genes, and methane mono-oxygenase (pmoA) genes from pure cultures and those cloned from marine sediments. In experiments using glass slide microarrays, genes possessing less than 80 to 85% sequence identity were differentiated under hybridization conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
262
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 354 publications
(278 citation statements)
references
References 37 publications
14
262
0
2
Order By: Relevance
“…When PCR-amplicon-based FGAs were used, the detection limit for nirS genes was approximately 1 ng of pure genomic DNA and 25 ng of soil community DNA without amplification of target templates (Wu et al, 2001). Studies with a 50-mer FGA showed that the detection limit without target template amplification ranges from 5-10 ng of pure genomic DNA and 50-100 ng in a mixture of genomic DNA from different organisms (Rhee et al, 2004;Tiquia et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When PCR-amplicon-based FGAs were used, the detection limit for nirS genes was approximately 1 ng of pure genomic DNA and 25 ng of soil community DNA without amplification of target templates (Wu et al, 2001). Studies with a 50-mer FGA showed that the detection limit without target template amplification ranges from 5-10 ng of pure genomic DNA and 50-100 ng in a mixture of genomic DNA from different organisms (Rhee et al, 2004;Tiquia et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Because the arrays contain probes from the genes with known biological functions, they will be useful in linking microbial diversity to ecosystem processes and functions. Several systematic experimental evaluations indicated that FGA-based microarrays can be used as specific, sensitive and potentially quantitative tools for detecting microbial populations and functional activities in natural settings (Wu et al, 2001(Wu et al, , 2006aTaroncher-Oldenburg et al, 2003;Rhee et al, 2004;Steward et al, 2004;Tiquia et al, 2004). However, one of the greatest challenges in using FGAs for detecting functional genes and/or microorganisms in the environment is to design oligonucleotide probes specific to the target genes/microorganisms of interest because sequences of a particular functional gene are highly homologous and/or incomplete, especially sequences derived from laboratory cloning of environmental samples.…”
Section: Introductionmentioning
confidence: 99%
“…[68,97,124,152,167,199]. Furthermore, PCR products can be used as probes for the functional gene arrays [31,191]. The inappropriate labeling of a substantial fraction of the PCR products (1-5%) can lead to poorly controlled microarrays, even when originating from prestigious research centers or commercial entities [89].…”
Section: Genome Fragmentsmentioning
confidence: 99%
“…pmoA, amoA, nifH, nirK, nirS). Many of these have been successfully applied on various microarray platforms [21,86,171,191]. The major limitation of these alternative marker genes is the limited organism coverage of published sequence databases.…”
Section: Marker Genes Used On Mdmsmentioning
confidence: 99%
See 1 more Smart Citation